HISTORICAL APPROACHES IN ISLAMIC STUDIES - Abdillah, Moh. Arvil (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2023)
The study of the Historical Approach is very important to study in more depth. This is because these studies never stop being debated. The aim of this article is to understand 3 things: First, the paradigm of the historical approach in Islamic studies. Second, internal and external factors that influence the Historical Approach in Islamic Studies. Third, positive and negative implications. From a historical approach in the study of Islam towards community life. The method used by Lebelary Research is a qualitative approach based on Islamic historical theory. Meanwhile, data collection is done by collecting articles and books related to the theme of historical printing and analyzing them using qualitative data analysis techniques. The results found were 3 things: First, the paradigm... there are 3 forms of historical approaches in Islamic studies: (1) social (2) biographical (3) civilization. Second, internal influences... There are 3 factors in the historical approach: (1) research methodology (2) historical sources (3) intellectual tradition. Externally, there are 3 factors that influence the historical approach: (1) politics (2) technology (3) culture. Third, the positive implications of a historical approach to the lives of Muslim communities are 3 things: (1) deeper understanding (2) openness to change (3) relevance to modern challenges. Meanwhile, there are 3 negative implications of the historical approach to people's lives: (1) limitations in interpretation (2) limitations in sources (3) potential for contextual misunderstandings. The conclusion is that this paper shows the urgency both theoretically, methodologically and practically.